Study of heat driven cooling cycle for automobile air conditioning - Ng, Mai Sheng (Nanyang Technological University, 2020)
A principal challenge of cooling science is the development of natural refrigerant based chiller for automobile air conditioning that is compact, almost free of moving parts, environmentally friendly and driven by low grade waste heat from the car engine. Water is considered as a refrigerant due to its relatively high latent heat of evaporation. The report deals with adsorption-based cooling system powered via the exhaust heat from the automobile engine. However, the currently used vapor compression system is not environmentally friendly and consumes energy. This project mainly focuses on (i) the design on new adsorbents for water adsorption so that the higher water uptake and transfer per adsorption-desorption cycle could be achieved for the relative pressure (P/Ps) ranging from 0.1 to 0.3, (ii) the characterization of adsorbents to understand the morphology and porous properties with their thermal stabilities, and (iii) the isotherms and kinetics under chiller operating conditions. Based on isotherms and kinetics data of various MOFs + water systems confirmed from experiments, a thermodynamic modelling is shown here to understand the working principles and simulate the performance parameters of adsorption chiller under various heating power of automobile or the driving heat source temperatures. The mass and heat exchange balances for each component of the chiller are presented in this report. Hence, the metal Organic Frameworks (MOFs) are chosen instead of the conventionally used silica gel, zeolites or activated carbon. Among a good number of MOFs, the novel aluminium maleamic (Al-MA) is considered due to its higher water transfer and faster kinetics. The performance parameters such as the coefficient of performance (COP), and the specific cooling power (SCP) are calculated for various cycle times and hot water temperatures. The simulation results showed that the proposed Al-MA MOFs + water assisted adsorption chiller possesses the COP of ~0.8 and the SCP of 0.68 under the running conditions of automobile engine.